Usun nawiasy i wykonaj redukcje wyrazow podobnych :
a) 4c-(3c+2)-10c =
b) 7x-8-(5x+6) =
c) 9y-(8-3y)+16 =
d) 5x-(2-4x)+8x-7 =
e) -(-5c-8)+6-9c =
f) 6(a+2b)-3(2a-3b) =
g) 4(b+3)+3(a-b) =
h) 7(b+c)-3(b+2c) =
i) 5a+4(a-1) =
j) 5a+3(a-2)+5b =
k)4(2b+0,5)-6b =
l) 2a+5(a-2)+5b =

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T15:51:40+01:00
A) 4c-(3c+2)-10c = 4c-3c-2-10c=-9c-2
b) 7x-8-(5x+6) =7x-8-5x-6=2x-14
c) 9y-(8-3y)+16 =9y-8+3y+16=12y+8
d) 5x-(2-4x)+8x-7 =5x-2+4x+8x-7=17x-9
e) -(-5c-8)+6-9c = 5c+8+6-9c=-4c+14
f) 6(a+2b)-3(2a-3b) =6a+12b-6a+9b=21b
g) 4(b+3)+3(a-b) =4b+12+3a-3b=b+15a
h) 7(b+c)-3(b+2c) =7b+7c-3b-6c=4b+c
i) 5a+4(a-1) =5a+4a-4=9a-4
j) 5a+3(a-2)+5b =5a+3a-6+5b=8a+5b-6
k)4(2b+0,5)-6b =8b+2-6b=2b+2
l) 2a+5(a-2)+5b =2a+5a-10+5b=7a+5b-10
19 4 19
2010-02-28T15:55:29+01:00
A) 4c-(3c+2)-10c =4c-3c-2-10c=-9c-2
b) 7x-8-(5x+6) =1x-8-5x-6=-4x-14
c) 9y-(8-3y)+16 =9y-8+3y+16=12y+8
d) 5x-(2-4x)+8x-7 =5x-2+4x+8x-7=17x-9
e) -(-5c-8)+6-9c =5c+8+6-9c=-4c-1
f) 6(a+2b)-3(2a-3b) =6a+12b-6a+9b=3b
g) 4(b+3)+3(a-b) =4b+12+3a-3b=b+12+3a
h) 7(b+c)-3(b+2c) =7b+7c-3b-6c=4b+c
i) 5a+4(a-1) =5a+4a-4=9a-4
j) 5a+3(a-2)+5b =5a+3a-6+5b=8a-6+5b
k)4(2b+0,5)-6b =8b+2-6b=2b+2
l) 2a+5(a-2)+5b = 2a+5a-10+5b=7a-10+5b
6 2 6